First principles study of the structural, electronic, mechanical and superconducting properties of WX (X=C, N). (February 2015) - Kavitha, M.; Sudha Priyanga, G.; Rajeswarapalanichamy, R.; Iyakutti, K.
Abstract: The structural, electronic, mechanical and superconducting properties of tungsten carbide (WC) and tungsten nitride (WN) are investigated using first principles calculations based on density functional theory (DFT). The computed ground state properties, such as equilibrium lattice constant and cell volume, are in good agreement with the available experimental data. A pressure induced structural phase transition is observed in both tungsten carbide and nitride, from a tungsten carbide phase (WC) to a zinc blende phase (ZB), and from a zinc blende phase (ZB) to a wurtzite phase (WZ). The electronic structure reveals that these materials are metallic at ambient conditions. The calculated elastic constants obey the Born-Huang criteria, suggesting that they are mechanically stable at normal and high pressure. Also, the superconducting transition temperature is estimated for the WC and WN in stable structures at atmospheric pressure. Highlights: Ground state properties of WC and WN are investigated. A sequence of structural phase transition is predicted under high pressure. Electronic structure reveals that these materials exhibit metallic behavior. Computed elastic moduli obey traditional mechanical stability condition. Among these two materials WC is found to be the hardest material.